KAJIAN ETNOBOTANI TUMBUHAN AREN (Arenga pinata Merr) DI DESA ALOR BESAR KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Julianti Peni; Andam Suriyati Ardan; Nikmah Nikmah; Arini Arini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study amis to examine the knowledge and utilization of the suger palm (Arenga pinnata) by the local community in Alor Besar Village, Alor Barat Laut District, Alor Regency. The sugar palm holds significant ecological, economic, and cultural value for the local people. The research employed a qualitative approach with data collection techniques including direct observation, semi-structured interviews, and documentation leaders, sugar palm farmers, and community members involved in processing palm products. The results show that almost all parts of the sugar palm are traditionally utilized, such as the sap for traditional drinks and palm sugar, fibers (ijuk) for brooms and roofing, leaves for food wrapping, and the trunk and roots for construction materials and handicrafts. These uses are not only economic in nature but also reflect local wisdom in preserving natural resources. However, challenges remain, such as the lack of natural regeneration of palm trees and low interest among the younger generation in managing this plant.